Intergenerational trauma and war-induced PTSD in Kosovo: insights from the Albanian ethnic group - Hyseni Duraku, Zamira; Jahiu, Genta; Geci, Donjeta (Frontiers in Psychology, 2023)
Introduction War has profound and deep-rooted ramifications for individuals and societies. War-induced post-traumatic stress disorder (PTSD) is highly prevalent in Kosovo. This study aimed to obtain insights into the prevalence of perceived PTSD symptoms and their relation to the traumatic experiences of two generations: parents (survivors of the Kosovo War) and youth (children born after the Kosovo War), with an emphasis on the Albanian ethnic group. These experiences were then compared to understand intergenerational trauma. The study also aimed to identify the factors affecting PTSD prevalence, the role of social support, and the participants’ experience with mental health services. Method A total of 237 Kosovar Albanians (121 parents, 116 youth) from all seven districts of Kosovo were included in this study. Study variables were measured using the PTSD Checklist, the Life Events Checklist, Criterion A, and the Multidimensional Scale of Perceived Social Support. Results The results revealed that the youth had significantly higher levels of perceived PTSD symptoms and lower levels of perceived support than their parents. Youth whose parents had PTSD were more prone to experiencing PTSD symptoms than those whose parents did not have PTSD. These youth also experienced significantly more traumatic situations, such as exposure to sudden violent death or accidental death, assault with a weapon, sexual assault, and captivity. Participants with perceived PTSD and lower perceived social support needed mental health interventions significantly more than those without PTSD symptoms. Discussion The findings emphasize the importance of addressing the intergenerational nature of PTSD and identifying factors affecting its prevalence, including social support and access to mental health services. The study underscores the need for a comprehensive approach to examine the complex and diverse nature of PTSD and its impact on individuals, families, and communities, especially in conflict-prone or conflict-affected societies.